Oczekiwania uczniów i ich rodziców związane z edukacją onkologiczną = The expectations of school students and their parents regarding oncological education - Marianna Charzyńska-Gula; Małgorzata Kanadys; Marzena Janczaruk; Zdzisława Szadowska-Szlachetka (Kazimierz Wielki University, 2015)
Charzyńska-Gula Marianna, Kanadys Małgorzata, Janczaruk Marzena, Szadowska-Szlachetka Zdzisława. Oczekiwania uczniów i ich rodziców związane z edukacją onkologiczną = The expectations of school students and their parents regarding oncological education. Journal of Education, Health and Sport. 2015;5(6):407-418. ISSN 2391-8306. DOI 10.5281/zenodo.18908 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A407-418 https://pbn.nauka.gov.pl/works/570209 http://dx.doi.org/10.5281/zenodo.18908 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 24.06.2015.   Oczekiwania uczniów i ich rodziców związane z edukacją onkologicznąThe expectations of school students and their parents regarding oncological education Marianna Charzyńska-Gula1, Małgorzata Kanadys2, Marzena Janczaruk3, Zdzisława Szadowska-Szlachetka1   • 1.       Katedra Onkologii i Środowiskowej Opieki Zdrowotnej Uniwersytet Medyczny w Lublinie / Department of Oncology and Community Health Care, Medical University of Lublin • 2.       Studenckie Koło Naukowe przy Katedrze Onkologii i Środowiskowej Opieki Zdrowotnej Uniwersytet Medyczny w Lublinie / Student Research Club at the Department of Oncology and Community Health Care, Medical University of Lublin • 3.       Centrum Onkologii Ziemi Lubelskiej / St John's Oncology Centre in Lublin   Adres do korespondencji / Address for correspondence dr n. med. Marianna Charzyńska-Gula / Marianna Charzyńska-Gula, MD, PhD jaligula@o2.pl   Streszczenie   Wprowadzenie: Świadomość istnienia czynników ryzyka powodujących powstanie choroby nowotworowej to bardzo znaczący element w walce z rakiem. Odpowiednie postawy i zachowania mogą w dużej mierze zapobiec rozwojowi choroby a także ograniczyć jej poważne następstwa. Szkolna edukacja onkologiczna to zadanie nowoczesnej profilaktyki chorób nowotworowych. Cel pracy: poznanie opinii uczniów i ich rodziców na temat realizacji w szkole edukacji onkologicznej. Materiał i metoda: Badano grupę 105 gimnazjalistów z miejskich i wiejskich gimnazjów oraz ich rodziców w liczbie 103 osób. Zastosowano metodę sondażu diagnostycznego z autorskim narzędziem w postaci kwestionariusza ankiety. Analizę ilościową przeprowadzono wykorzystując test U Manna-Whitneya oraz test jednorodności i niezależności Chi2 (χ2). Wyniki badań: Rodziców częściej niż młodzież interesują zagadnienia dotyczące profilaktyki chorób nowotworowych, a także niepokojących objawów, natomiast dla młodzieży ważniejsza jest etiologia tych chorób. Dla rodziców najważniejszym źródłem informacji na temat chorób nowotworowych jest pielęgniarka szkolna (ok. 58%), natomiast taką pozycję nadaje jej tylko ok. 18% uczniów. Siebie jako dobre źródło tych informacji uznaje ok. 50% badanych rodziców co nie znajduje potwierdzenia w opinii ich dzieci (ok. 19%). Opinie nt. form przekazu wiedzy onkologicznej były podobne a największa różnica dotyczyła rozmowy i pogadanki - uczniowie cenią je mniej niż rodzice. Młodzież - w przeciwieństwie do rodziców - uważa, że wiedza onkologiczna nie powinna być sprawdzana, ponieważ jest to sprawa indywidualna każdego ucznia. Młodzież częściej niż rodzice uważa, że skuteczność edukacji zależy od osoby edukowanej i jej stosunku do edukacji, a nie od sposobu przekazywanej wiedzy (ok.75%). Wnioski: Mimo, że respondentami byli członkowie tych samych rodzin, to opinie dotyczące szkolnej edukacji onkologicznej w znacznej części były wyraźnie różne. Różnice te dowodzą potrzeby wprowadzenie do szkół programowych elementów informacji o nowotworach uwzględniających jednak dwie grupy odbiorców - uczniów i ich rodziców.   Słowa kluczowe: szkoła, edukacja onkologiczna, uczniowie, rodzice.   Abstract   Background: The awareness of cancer risk factors is a crucial factor in combatting cancer. The right approaches and behaviour can largely contribute to preventing cancer development and limiting its serious consequences. Oncological education at school is one of the objectives of modern cancer prevention. Objective: To recognise the opinions of students and their parents on the implementation of oncological education at school. Material and methods: The survey included 105 lower-secondary school students from urban and rural areas and 103 of their parents. The diagnostic survey method was applied with the use of the questionnaire prepared by the authors. The quantitative analysis was carried out using the Mann-Whitney test and the Chi2 (χ2) homogeneity and independence test. Results: The parents more often than their children were interested in issues associated with cancer prevention and identifying alarming symptoms, while for the young people the etiology of neoplastic diseases was of central importance. For the parents the major source of information on neoplasms was the school nurse (approx. 58%), while the percentage of the students sharing the same opinion was only 18%. Approx. 50% of the surveyed parents considered themselves a good source of information on the issue, which, however, was not confirmed in their children's opinions (approx. 19%). The views on the forms of communicating oncological knowledge were similar, and the most substantial difference referred to conversations and lectures, which were valued by the students lower than by their parents. The young people, contrary to their parents, claimed that knowledge on oncology should not be tested as it is a private matter of each student. The students more often than their parents claimed that the effectiveness of education depends on the person receiving it rather than on the method of communicating knowledge (approx. 75%). Conclusions: Despite the fact that the respondents belonged to the same families, their opinions on oncological education at school differed considerably. The differences demonstrate the need to include in school curricula the elements of knowledge on neoplasms for two separate groups of recipients - students and their parents.   Key words: school, oncological education, school students, parents.